Analysis of Full Cost Calculation and Activity-Based Cost Calculation Methods as A Basis for Designing Marketing Strategies for Product Package Pricing - Naufal Hanif Pratama; Anindya Rachma Dwicahyani (Jurnal Teknologi dan Manajemen, 2027)
Accurate determination of Cost of Goods Sold (COGS) is a key pillar in setting competitive selling prices for the sustainability of the culinary business. However, Depot Sekar Sari faces the challenge of stagnant monthly revenue due to a conventional cost accounting system based on the owner's intuition, where overhead cost components such as electricity, gas, water, and equipment depreciation have not been allocated proportionally to each menu. To overcome this obstacle, this study compares cost calculations using the Full Costing and Activity Based Costing (ABC) methods. The results of data processing show that the ABC method has a higher level of accuracy in revealing cost distortions compared to the traditional method. The traditional method is proven to trigger overcosting on the main chicken menu with a difference of IDR 3,000–IDR 4,000, and undercosting on the rice and beverage menu with a difference of IDR 141–IDR 1,000. The results of this accurate ABC COGS calculation are then integrated with the STP (Segmentation, Targeting, Positioning) marketing framework to formulate a promotional program strategy in the form of 6 variants of product bundling schemes (family and individual packages) with a 10% package discount. This integrative implementation has proven effective in providing a fair pricing structure for customers while stimulating the average daily transaction value (average transactions per transaction) to increase total profitability and overcome Depot Sekar Sari's financial stagnation.